2010
DOI: 10.1186/1742-4933-7-6
|View full text |Cite
|
Sign up to set email alerts
|

BELFAST nonagenarians: nature or nurture? Immunological, cardiovascular and genetic factors

Abstract: Nonagenarians are the fastest growing sector of populations across Western European and the developed world. They are some of the oldest members of our societies and survivors of their generation and may help us understand how to age not only longer, but better.The Belfast Longevity Group enlisted the help of 500 community-living, mobile, mentally competent, 'elite' nonagenarians, as part of an ongoing study of ageing. We assessed some immunological, cardiovascular, nutritional and genetic factors and some asp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 70 publications
4
16
0
Order By: Relevance
“…Although the alterations of NK cells and other innate immune cells with aging are generally less marked than those seen with T cells [16,54], we observed that in our subjects, a greater correlation with age was found for NK cells (r 2  = +0.21, p = 0.0002) than for CD4/CD8 ratio (r 2  = +0.14, p = 0.01). A similar positive correlation between age and CD4/CD8 ratio in Irish individuals was reported by Rea et al [4]. Moreover, we observed a shift from a predominance of naïve T cells towards T cells expressing memory phenotypes from the youngest to the oldest age groups, as previously reported [12,55].…”
Section: Discussionsupporting
confidence: 91%
“…Although the alterations of NK cells and other innate immune cells with aging are generally less marked than those seen with T cells [16,54], we observed that in our subjects, a greater correlation with age was found for NK cells (r 2  = +0.21, p = 0.0002) than for CD4/CD8 ratio (r 2  = +0.14, p = 0.01). A similar positive correlation between age and CD4/CD8 ratio in Irish individuals was reported by Rea et al [4]. Moreover, we observed a shift from a predominance of naïve T cells towards T cells expressing memory phenotypes from the youngest to the oldest age groups, as previously reported [12,55].…”
Section: Discussionsupporting
confidence: 91%
“…Subjects willing to enrol, were community-living, mobile, and mentally competent (mini mental score examination > 26/30), (Folstein et al 1975 ) and gave written consent. Briefly, subjects gave blood samples for DNA and other laboratory variables, responded to nutrition, life style and medical history questionnaires, blood pressure and anthropometric measurements (Rea et al 2009 ) and provided self-directed narrative life-stories (Ganzevoort and Bouwer 2007 ) together with structured questions (Rea and Rea 2011 ; Rea Maeve 2013 ). Ethical permission for the Belfast Elderly Longitudinal Free-Living Ageing STudy (BELFAST) studies was given by Research Ethics Committee Northern Ireland (ORECNI), 08/NIR03/42 and by The Queens University Belfast.…”
Section: Methodsmentioning
confidence: 99%
“…However, 90 year olds are both the fastest growing sector of present day populations and the group about whom we know relatively little medically, socially and economically. It can be argued that they are of special interest because of their extreme age and because in this study they were well categorised by Senieur status (Rea et al 2009; Rea 2010; Lighthart et al 1984). Studies in this age group are extremely challenging because of perceived or real frailty and the understandable concern of the subjects themselves, relatives, researchers and Ethical Committees not to exploit, tire or over-ride the autonomy of the subject group (Samelson et al 2008).…”
Section: Discussionmentioning
confidence: 81%
“…Elderly subjects were a consecutive mid-study cohort enlisted from the BELFAST study, aged 80–100 years of age (Rea 2010; Rea et al 2009), who met SENIEUR protocol (Ligthart et al 1984). At recruitment, all subjects were mentally alert (Folstein >25/30), (Folstein and Folstein et al 1975), apparently well and living in the community.…”
Section: Methodsmentioning
confidence: 99%